The Construction History and Photo Scanner Survey of the Minorite Church in Nyírbátor - Turi, Olivér (International Journal of Engineering and Management Sciences, 2023)
The medieval Minorite church of Nyírbátor suffered serious damages and became abandoned at the end of the 17th century. In the 18th century, the baroque reconstruction of the church began, and later a second period of Baroque modifications took place. After this, the church remained untouched for a long time. Then, in the 20th century once again renovations were deemed necessary, because of its poor condition at the time. During the 19th and until the end of the 20th century, several restoration works and archaeological excavations took place, which focused on certain aspects of the church. In this article, I would like to present a summary of the notes concerning the construction history of the church and the results and methods of the photo scanner survey I carried out.